Kybersodankäynnin menetelmät ja haavoittuvuus - Suontausta, Joona (2025)
Almost every information system in modern society is connected to a network, making it part of the digital environment, or cyber environment. Connectivity and the spread of information technology also bring growing risks with them. This means huge amounts of vulnerabilities in information systems, and the vulnerabilities are not limited to technology itself. In addition, personnel and organizational processes need to be updated in the field of cybersecurity to suppress vulnerabilities. There are different types of users in the cyber environment, and some are ready to exploit this environment as part of warfare. This is called cyber warfare. It refers to cyber-attacks conducted by state actors or an APT group operating with state funding. These attacks have a political objective and affect, for example, infrastructure, information management, and the safety of citizens. It has been noted from the war in Ukraine that Russia has sought to undermine Ukraine’s critical infrastructure with cyber-attacks. This thesis aimed to develop an understanding of the actors in cyber warfare and to describe the methods and tactics they use. The thesis also assessed the threats posed by actors and their motivations. This thesis delved into the capabilities of the attacker from the perspective of critical infrastructure protection. The goal was to determine how vulnerabilities are managed as part of national cyber defense and organizational cybersecurity. This master’s thesis has been conducted as a qualitative study. The phenomenon at the center of qualitative research should be examined from as many different perspectives as possible. The topic and research problem of the thesis is limited and determined by the material and its analysis method. The study was based on a factual perspective because the study is interested in the information that the available material reveals about the research object. The analysis of the material was conducted as a content analysis. The results of the study were analyzed using two case studies using an assessment tool. The results showed that vulnerabilities in critical systems can be managed and minimized if all areas are in order in the organization’s operations. If even one area is poorly considered or its level is non-existent, it opens a new attack vector for the attacker. Risk management and cyber resilience are influential factors in managing vulnerabilities in critical systems. The most common cyber vulnerabilities targeting critical systems are often found through weaknesses in the target systems.